Strategi Pemasaran Media Indonesia Untuk Meningkatkan Penjualan Space Iklan di Website Mediaindonesia.com di Era Digital - Yudi Prasetio; Eko Harry Susanto (Jurnal Manajemen Bisnis dan Kewirausahaan, 2020)
The purpose of this research is to find out the efforts made by Koran Media Indonesia in facing the digital era by making new innovations in the digital world, namely making the website www.mediaindonesia.com so that the readers of Media Indonesia are growing and clients are still willing to advertise in Media Indonesia both in Print or online. The benefit of this research is to be able to provide information, views and advice for companies engaged in print and advertising media such as Indonesian media, so that Media Indonesia can still get revenue other than Media Indonesia newspaper sales, and also from companies that advertise in Media Indonesia both in print and online. From the research results, it shows that the marketing strategy from mediaindonesia.com is more appropriate to use product development, market penetration and market development strategies. With these results, mediaindonesia.com is advised to utilize resources, internal and external strengths, as well as opportunities and threats to further develop products, market penetration and market development. If the strategy has been successfully carried out, it is hoped that the objectives of the company will be achieved, namely by adding revenue to the company.